QTL for Main Stem Node Number and Its Response to Plant Densities in 144 Soybean FW-RILs - Li, Wen-Xia; Wang, Ping; Zhao, Hengxing; Sun, Xu; Yang, Tao; Li, Haoran; Hou, Yongqin; Liu, Cuiqiao; Siyal, Mahfishan; Raja veesar, Rameez; Hu, Bo; Ning, Hailong (Frontiers in Plant Science, 2021)
Node number of main stem (NNMS) is an important yield related trait for soybean [Glycine max (L.) Merr.], it was affected by density. Here, a four-way recombinant inbred lines (FW-RIL) with 144 families derived from Kenfeng 14, Kenfeng 15, Heinong 48, Kenfeng 19 was used to identified QTL/QTN for NNMS and its response to density under 2.2×105 plant/ha and 3×105 plant/ha in five environments by linkage analysis and GWAS. The results showed that the response of NNMS to densities was significantly different, a total of 16 QTL and 34 QTN were identified specifically in D1; 10 QTL and 18 QTN were identified specifically in D2; Five QTL was found commonly in two densities; 7 QTL and 29 QTN single identified for response to density, 7 QTL and 5 QTN response to density associated with the QTL and QTN that identified in D1 or D2. In the whole QTL and QTN, 12 QTL and 19 QTN were repeatedly detected by multiple methods, densities, environments, and explained phenotypic variation more than 10%. In addition, 24 QTN co-located with QTL, 15 of them explained phenotypic variation more than 10%. Finally, genes underlying related to NNMS were predicted, which were Glyma.06G094400, Glyma.06G147600, Glyma.19G160800.1 and Glyma.19G161100. These findings will help elucidate the genetic basis of NNMS and improve molecular assistant selection of high-yield soybean.